2020
DOI: 10.1182/bloodadvances.2020001800
|View full text |Cite
|
Sign up to set email alerts
|

The dual PI3Kδ/CK1ε inhibitor umbralisib exhibits unique immunomodulatory effects on CLL T cells

Abstract: Abstract The in-clinic phosphatidylinositol 3-kinase (PI3K) inhibitors idelalisib (CAL-101) and duvelisib (IPI-145) have demonstrated high rates of response and progression-free survival in clinical trials of B-cell malignancies, such as chronic lymphocytic leukemia (CLL). However, a high incidence of adverse events has led to frequent discontinuations, limiting the clinical development of these inhibitors. By contrast, the dual PI3Kδ/casein kinase-1-ε (CK1ε) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 37 publications
6
64
1
Order By: Relevance
“…In line with these observations, CK1ε inhibition was able to block cartilage destruction in the mouse osteoarthritis model [137]. In addition, CK1 inhibition can modulate T cells-CK1δ was shown to be essential for the formation of the immunological synapse [140] and CK1ε inhibition by umbralisib and PF-4800567 could protect Tregs and prevent immune system mediated toxicities in CLL patients treated with PI3K inhibitors [96,133].…”
Section: Summary and Future Directionsmentioning
confidence: 56%
See 3 more Smart Citations
“…In line with these observations, CK1ε inhibition was able to block cartilage destruction in the mouse osteoarthritis model [137]. In addition, CK1 inhibition can modulate T cells-CK1δ was shown to be essential for the formation of the immunological synapse [140] and CK1ε inhibition by umbralisib and PF-4800567 could protect Tregs and prevent immune system mediated toxicities in CLL patients treated with PI3K inhibitors [96,133].…”
Section: Summary and Future Directionsmentioning
confidence: 56%
“…Two recent studies have assessed the possible contribution of CK1ε inhibition to the clinical effects of umbralisib by comparing umbralisib to duvelisib and/or idelalisib, two approved PI3K inhibitors devoid of CK1 inhibitory activity [57,96]. In the first study, authors asked why umbralisib and not idelalisib showed specific cytotoxicity in CLL, lymphoma and myeloma cells when combined with proteasome inhibitor carfilzomib [57].…”
Section: Umbralisib a Dual Pi3kδ-ck1ε Inhibitor Demonstrates Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Weerdt et al reported that after 1 year of venetoclax-based therapy, frequencies of tumor-supportive T-follicular helper cells, Tregs and PD-1 + CD8 + T cells were significantly decreased in CLL patients (40). Other studies have demonstrated that inhibition or silencing of PI3Kd in preclinical CLL models modulates T-cell subsets, particularly Tregs (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%